1990
DOI: 10.1073/pnas.87.19.7618
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of autoimmune diabetes and thyroiditis to athymic rats.

Abstract: We describe the induction of autoimmune diabetes, insulitis, and thyroiditis in athymic rats following ujections of major histocompatibiity complex compatible spleen cells. Lymphocytes with these capabilities were found in normal rats ofthe YOS, WAG, PVG, and diabetes-resistant BB strains, and in diabetes-prone BB rats. Adoptive transfer was facilitated by prior in vivo depletion of RT6.1+ regulatory T cells and in vitro mitogen activation of donor spleen cells. By RT6 depleting diabetes-resistant donors and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 22 publications
3
37
0
Order By: Relevance
“…Thus, a clear autoaggressive potential of CD4 + T cells was seen, in line with several studies on BB-DP rats and NOD mice [7][8][9][10][11][12]. The predominant role of CD4 + T cells has been previously demonstrated by selective transfer of CD4 + or CD8 + T cells in immunodeficient NOD strains, whereas CD8 + T cell subsets were not diabetogenic [7,16].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Thus, a clear autoaggressive potential of CD4 + T cells was seen, in line with several studies on BB-DP rats and NOD mice [7][8][9][10][11][12]. The predominant role of CD4 + T cells has been previously demonstrated by selective transfer of CD4 + or CD8 + T cells in immunodeficient NOD strains, whereas CD8 + T cell subsets were not diabetogenic [7,16].…”
Section: Discussionsupporting
confidence: 85%
“…The only difference between the LEW.1AR1-iddm rat and the background strain is a mutation on chromosome 1 within Iddm8 (RNO1q43-51) [4,5]. Adoptive transfer of T cells from diabetic LEW.1AR1-iddm rats to prediabetic LEW.1AR1-iddm rats significantly increased the incidence of diabetes [6] in agreement with studies on NOD mice and BB-DP rats [7][8][9][10][11][12]. The autoreactive potential can be transferred through immune cells from diabetic LEW.1AR1-iddm rats into athymic nude LEW.1AR1-Whn rnu animals, but not to the diabetes-resistant LEW.1AR1 background strain [6].…”
Section: Introductionsupporting
confidence: 79%
“…Thirty years ago, it was proposed that subsets of thymus-derived CD4 T cells are essential to actively suppress immune responses and maintain self-tolerance (1)(2)(3). Recent studies have identified specific regulatory T cells that likely explain these phenomena (4)(5)(6)(7). Subsets of regulatory T cells have been described, and they share common features of being hypoproliferative to T cell antigen receptor (TCR) stimulation in vitro and immunosuppressive in vitro and in vivo.…”
Section: Regulatory T Cells ͉ Tgf-␤mentioning
confidence: 99%
“…Attempts were made to separate the two putative CD4 + populations in normal naive mice by the expression of cell surface molecules [20][21][22][23][24][25][26] (Fig. 1C).…”
Section: Naturally Arising Cd25mentioning
confidence: 99%